A wireless sensor network coverage optimization algorithm based on particle swarm optimization and Voronoi diagram - Ab Aziz, Nor Azlina; Alias, Mohamad Yusoff; W. Mohemmed, Ammar (IEEE Xplore, 2009)
The coverage problem is a crucial issue in wireless sensor networks (WSN), where a high coverage rate ensures a high quality of service of the WSN. This paper proposes a new algorithm to optimize sensor coverage using particle swarm optimization (PSO) and Voronoi diagram. PSO is used to rind the optimal deployment of the sensors that gives the best coverage while Voronoi diagram is used to evaluate the fitness of the solution. The algorithm is evaluated through simulation in different WSN. The simulation results show that the proposed algorithm achieves a good coverage with a better time efficiency.